CORS architecture and evaluation of positioning by low-cost GNSS receiver - Pepe, Massimiliano (Geodesy and Cartography, 2018)
In recent years, the use of low cost GNSS receivers is becoming widespread due to their increasing performance in the spatial positioning, flexibility, ease of use and really interesting price. In addition, a recent technique of Global Navigation Satellite System (GNSS) survey, called Network Real Time Kinematic (NRTK), allows to obtain to rapid and accurate positioning measurements. The main feature of this approach is to use the raw measurements obtained and stored from a network of Continuously Operating Reference Stations (CORS) in order to generate more reliable error models that can mitigate the distance-dependent errors within the area covered by the CORS. Also, considering the huge potential of this GNSS positioning system, the purpose of this paper is to analyze and investigate the performance of the NTRK approach using a low cost GNSS receiver, in stop-and-go kinematic technique. By several case studies it was shown that, using a low cost RTK board for Arduino environment, a smartphone with open source application for Android and the availability of data correction from CORS service, a quick and accurate positioning can be obtained. Because the measures obtained in this way are quite noisy and, more in general, increasing with the baseline, by a simple and suitable statistic treatment, it was possible to increase the quality of the measure. In this way, this low cost architecture could be applied in many geomatics fields. In addition to presenting the main aspects of the NTRK infrastructure and a review of several types of correction, a general workflow in order to obtain quality data in NRTK mode, regardless of the type of GNSS receiver (multi constellations, single or many frequencies, etc.) is discussed.